Health efficiency : how can engineering be a player in health organization? - Sarazin, Marianne (Elsevier Ltd. : ISTE Press, 2018)
Efficiency is an important component of performance measurement. It is the optimization of the consumption of the resources used for the production of a result. From this conception was born the idea of these days devoted, each year, to the efficiency applied to the world of health. They brought together researchers, doctors and engineers involved in the same reflection on this problem. Collaborations between doctors and engineers are more and more numerous. However, the application of industrial engineering and operational research to health systems is still poorly known in the medical world and it seemed important to offer this community a meeting place with the world of engineering. These days have been the subject of many exchanges that have allowed a better knowledge between health professionals and engineers, part of which is presented in this book.